Activation of MAPK pathways due to DUSP4 loss promotes cancer stem cell-like phenotypes in basal-like breast cancer - Balko, JM (2020)
Basal-like breast cancer (BLBC) is an aggressive disease that lacks a clinically approved targeted therapy. Traditional chemotherapy is effective in BLBC, but it spares the cancer stem cell (CSC)-like population, which is likely to contribute to cancer recurrence after the initial treatment. Dual specificity phosphatase-4 (DUSP4) is a negative regulator of the mitogen-activated protein kinase (MAPK) pathway that is deficient in highly aggressive BLBCs treated with chemotherapy, leading to aberrant MAPK activation and resistance to taxane-induced apoptosis. Herein, we investigated how DUSP4 regulates the MAP-ERK kinase (MEK) and c-jun-NH2-kinase (JNK) pathways in modifying CSC-like behavior. DUSP4 loss increased mammosphere formation and the expression of the CSC-promoting cytokines interleukin (IL)-6 and IL-8. These effects were caused in part by loss of control of the MEK and JNK pathways and involved downstream activation of the ETS-1 and c-JUN transcription factors. Enforced expression of DUSP4 reduced the CD44(+)/CD24(-) population in multiple BLBC cell lines in a MEK-dependent manner, limiting tumor formation of claudin-low SUM159PT cells in mice. Our findings support the evaluation of MEK and JNK pathway inhibitors as therapeutic agents in BLBC to eliminate the CSC population.